Investigation of the Influence of Warhead Shape and Type of Missile Weapon Material Counter-Training Tank Weapons Simulation Approach - Budiarta, Transisma; Puspito Buwono, Haris; Nurvian Amrullah, Radhi (Universitas Negeri Malang, 2025)
This study analyzes the effect of warhead shape and material variations on pressure, temperature, and lift on training missiles using CAD-based simulation methods. The variations of warhead shapes tested include flat, flat radius, and tapered, while the materials used are rubber, ABS, and PE. The simulation results show that the tapered warhead shape with PE material produces the lowest pressure (50.3 MPa) due to more efficient pressure release and low friction properties. Conversely, the Flat shape produces the highest pressure (69.1 MPa) on all materials due to flow stagnation. In terms of temperature, the Flat Radius warhead with PE and Rubber materials has the lowest temperature ( 335.56 K) due to flow expansion and low thermal conductivity, while the Tapered warhead with PE has the highest temperature (336.07 K) due to increased fluid velocity, which causes an adiabatic effect. In terms of lift, the tapered warhead with rubber shows the highest value (72.397) due to interaction with the turbulent boundary layer, while the flat radius warhead with rubber has the lowest lift (67.420) due to faster flow separation. These results can be applied in the optimization pf training missile design, jet warhead systems, and aerodynamic vehicles. Further development can include the exploration of alternative materials and the integration of advanced simulation technologies to improve the aerodynamic efficiency and durability of materials.